2012
DOI: 10.4314/wsa.v38i2.8
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration and runoff losses under fallowing and conservation agriculture practices on contrasting soils, Zimbabwe

Abstract: Fallowing and conservation agriculture are sustainable farming practices that can be used for soil and water conservation. The objectives of the study were to evaluate the effects of different conservation agriculture practices on rainfall infiltration and soil and water losses across 4 sites, using simulated rainfall. The study was carried out at Domboshawa and the Institute of Agricultural Engineering and Chikwaka smallholder farming areas, 4 sites with different soil types. Conservation agriculture practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 26 publications
(19 reference statements)
2
35
0
1
Order By: Relevance
“…Runoff was summed, if it was measured multiple times in a growing season or by multiple rainfall runs, or was determined separately in wheeled and non-wheeled areas. One study in which runoff was zero in some treatments was excluded (Nyamadzawo et al, 2012), as zero values are not suitable for the present meta-analysis that used the response ratio as the effect size (Hedges et al, 1999). In order to examine the temporal trend in the effectiveness of NT, studies that reported only average runoff across multiple years were excluded.…”
Section: Data Collectionmentioning
confidence: 99%
“…Runoff was summed, if it was measured multiple times in a growing season or by multiple rainfall runs, or was determined separately in wheeled and non-wheeled areas. One study in which runoff was zero in some treatments was excluded (Nyamadzawo et al, 2012), as zero values are not suitable for the present meta-analysis that used the response ratio as the effect size (Hedges et al, 1999). In order to examine the temporal trend in the effectiveness of NT, studies that reported only average runoff across multiple years were excluded.…”
Section: Data Collectionmentioning
confidence: 99%
“…Although the role of no-till as a climate-smart solution is being questioned [1][2][3], the technology still remains one of the solutions to address some of the challenges affecting small-scale farming in Africa [1]. Amongst the major challenges faced by small-scale farmers are soil erosion and the efficiency in which the limited water is used [4][5][6]. The situation is further worsened by climate change effects such as persistent droughts, which are currently being experienced in the sub-Saharan region [5].…”
Section: Introductionmentioning
confidence: 99%
“…Amongst the major challenges faced by small-scale farmers are soil erosion and the efficiency in which the limited water is used [4][5][6]. The situation is further worsened by climate change effects such as persistent droughts, which are currently being experienced in the sub-Saharan region [5]. Agriculture remains one of the most important components of most African economies [7] and its success is based on the foundation of good soils and efficient utilization of the available water resources, among other factors.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has been conducted into the broader frameworks of integrated soil fertility management [130][131][132][133][134][135][136][137], conservation agriculture [138][139][140][141][142][143], erosion control [144][145][146][147][148], and improved grazing management [149][150][151]. There is also a wealth of information on the benefits of specific practices such as short legume rotations (improved fallows) [152][153][154][155][156][157][158], agroforestry systems [159][160][161][162][163][164][165], and no-till systems [166][167][168][169][170]. Most of these studies, however, are short-term and geographically limited.…”
Section: Positive Trajectories and Conclusionmentioning
confidence: 99%